A lousa digital interativa: um estudo de caso no Instituto Federal de São Paulo - Silva, Fernanda Pereira da (2016)
This research has as object the Digital Whiteboards Interactive. The general objective is to analyze the Digital Whiteboards from the perspective of students and a teacher of high school. Specific objectives we list the following: check how the teacher and students use the whiteboard Digital, analyze how the Slate Digital contributes or not to an interactive lesson. We seek to answer the following question: The Digital Whiteboards favor interactivity between students and the teacher of high school? The research was conducted at the Federal Institute of Education, Science and Technology of São Paulo (IFSP), Campus São Paulo, located in the north of the city. The subjects were 10 students and the teacher of Portuguese Language Literature course the average level of course integrated into the technical course in mechanics. This is a qualitative research of the case study type and data collection procedures was semistructured interviews with teachers, focus group with students and observe the lessons of the discipline of Portuguese Language Literature. To support the category of Information and Communication Technology (ICT) resorted to Pinto (2005), Lèvy (1993, 1996, 2000), Kenski (2003a, 2003b, 2006, 2007, 2011); Moran (2013), and Mazetto (2013); to support the interactive class and learning categories used Freire (1996, 1982, 1987), Silva (2006), Santaela (2004) and McLuhan (1964). In support of culture category and digital culture resorted to Lipovetsky and Serroy (2011) and Levy (2000). It concludes with this work that Digital Blackboards make the most interactive lessons, favor the process of teaching / learning, promoting greater interaction among individuals, enabling reflective thinking and critical awareness of reality and understanding of the responsibilities. Contribute to the understanding of content, and when associated with objectives and pedagogical practices are enablers for the teacher and students. The students point out that the tool makes sense, since there is prior planning of the teacher and the same know how to use all the features offered by Digital Whiteboard. Professor says that technology is an important tool, but it does not replace the human relationship between teacher and student.